Performance prediction of biomimetic adaptive building skins: Integrating multifunctionality through a novel simulation framework. (August 2021) - Kuru, Aysu; Oldfield, Philip; Bonser, Stephen; Fiorito, Francesco
Highlights: A novel method to simulate multifunctional biomimetic adaptive facades is proposed. Multifunctional adaptive facades can be simulated with script-based controls. 600 iterations of a multifunctional shading and ventilating Bio-ABS is analysed. PVC glazing achieves shading, and SMA springs trigger ventilation by openings. An adaptive façade over a non-adaptable one improves thermal comfort by 18 to 37.1%. Abstract: Biomimetic adaptive building skins (Bio-ABS), being adaptable to changing environmental conditions, can foster improved comfort and reduced energy demand. Bio-ABS are climate-adaptable façades, and biological functions inspire their design. Buildings often require multiple functions for improved environmental performance. Multifunctionality refers to hosting multiple triggered by diverse stimuli interdependently. The realisation of multifunctional Bio-ABS may be challenging due to difficult construction processes, expensive materials, and the complexity in their application. Thus, digital modelling and simulation of multifunctional Bio-ABS are important to predict their performance. This paper reviews the studies on simulating Bio-ABS, proposes a novel simulation framework for multifunctional Bio-ABS and demonstrates it through a parametric case study. Performance comparisons among twenty base-case scenarios and 600 iterations of shading and ventilating multifunctional Bio-ABS provides shading through photovoltachromic (PVC) glazing and ventilation through Shape Memory Alloy (SMA) springs triggered openings. It is multifunctional by changing its morphology and physiology due to photovoltachromic glazing triggered by solar irradiance and Shape Memory Alloys being triggered by temperature. The results show that Bio-ABS improves building performance when compared against non-adaptable façades, reaching 37.1% for 90% acceptability limits and 18% for 80% acceptability limits for adaptive thermal comfort in an educational building in the humid subtropical climate of Sydney. Australia. The main outcome and contribution of this study is a novel simulation framework to predict the performance of morphology and physiology changing multifunctional Bio-ABS. Future work may focus on prototyping and validated experiments to close the gap between theory and the real world.